Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development se ctor in the past decade is partly a response to the complex and interc onnected challenges facing many developing countries, including the im pacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, econ omic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governme nts to experiment with different entry points and to adapt or change c ourse when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen sy stems of planning and delivery for adaptation to climate change in Sou th Asia. As the programme draws to a close, this Learning Paper reflec ts on some of the major lessons learnt on the challenges and opportuni ties of using an adaptive programme management approach to support gov ernments to adapt to climate change. The authors are members of the AC T implementation team, representing the management, operational and te chnical teams, from across different locations. The paper therefore re flects their first-hand account of the reality of implementing adaptiv e programmes. The paper sets out a framework for the essential ingredi ents of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and lear ning; and stakeholder alignment. It also includes two sets of essentia l resources required: management flexibility and adequate financial re sources. The paper then provides learning from ACT on how to operation alise these core principles and mobilise the necessary resources. It g ives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, a s well as retrospective reflections of additional actions the programm e could have taken. A set of case studies unpacks how adaptive program me management has been operationalised in practice in particular locat ions. The authors are confident that the impact ACT has had owes in la rge part to it being an adaptive programme. The programme’s flexibilit y, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerge d and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT ha s faced as an adaptively managed programme. The paper therefore conclu des with a set of lessons learnt from ACT for the benefit of others de signing and delivering adaptive programmes on climate change and other issues.